The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1964
DOI: 10.1002/aic.690100214
|View full text |Cite
|
Sign up to set email alerts
|

Hydrates at high pressures: Part I. Methane‐water, argon‐water, and nitrogen‐water systems

Abstract: qi,qz,qi,qz = General quantities given by Equation (S), SM' = S M / d R = r = rt = a = rm = s = T = T = Ti = Tz = N T~ = -NTa* = .. v * A Part I ratio of cylinder speeds radius or coordinate radius of inner cylinder radius of outer cylinder mean radius shape function given by Equation (23), Part I temperature average temperature in annulus temperature of inner cylinder temperature of outer cylinder Taylor number Tavlor number ( \ i N~a " __-N T~~ = t = tl= u = u 1 = us = o = 0 1 = o = -. w = w1 = z = z = , . N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
106
1

Year Published

1964
1964
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(117 citation statements)
references
References 7 publications
10
106
1
Order By: Relevance
“…(2) shows the pressure temperature relations of Ar hydrate system accompanied with the literature values [3,18]. In the low-pressure region (up to 200 MPa), our data are in good agreement with Marshall's ones [18]. Moreover, except less than 20 MPa, the present data are in almost agreement with Dyadin's ones [3].…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…(2) shows the pressure temperature relations of Ar hydrate system accompanied with the literature values [3,18]. In the low-pressure region (up to 200 MPa), our data are in good agreement with Marshall's ones [18]. Moreover, except less than 20 MPa, the present data are in almost agreement with Dyadin's ones [3].…”
Section: Resultssupporting
confidence: 87%
“…The region A corresponds to the pressure range up to 281 MPa. The pressure range from 281 to 456 MPa is region B, and over 456 MPa defined as region C. Especially, in the region B, the present data show the large discrepancies with the literature [3,18]. The Raman spectrum of intermolecular O-O stretching vibration mode of water molecules was detected around 210 cm -1 in the structure-II gas hydrate systems; we have already reported about N 2 and SF 6 hydrate systems [19,20].…”
Section: Resultscontrasting
confidence: 78%
See 1 more Smart Citation
“…A CO 2 -methane-water hydrate is stable at higher temperatures or lower pressures than a pure methane-water hydrate and thus could not account for an upward translation of the hydrate stability field. Likewise, at constant temperature, a natural gas-water hydrate is stable at much shallower depths than a methane-water hydrate (Marshall et al, 1964). For example, a 10% addition of ethane to a pure methane hydrate at 15°C would shift the phase boundary from 140 bar to 75 bar (Katz et al, 1959).…”
Section: Hydrates At Cascadia Marginmentioning
confidence: 99%
“…Sarupria compared the MD simulations result with experimental data, and found that the difference in the melting points (T m (hydrate)-T m (ice)) that was obtained from MD simulations is in good agreement with the experimental value. Under the experimental conditions, the hydrate melting point at 30 MPa is 295 K [61], 22 K higher than the melting point of Ice Ih. The melting point of SPC model is 190 K at 30 MPa, the corresponding hydrate melting point is about 212 K. In our simulation work, the temperature range of 243 K-263 K is higher than the melting point of both Ice Ih and hydrate at 30 MPa.…”
Section: Simulation Detailsmentioning
confidence: 95%